2013
DOI: 10.1155/2013/408670
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Instability Induced by Superselective Angiography of the Ophthalmic Artery

Abstract: Retinoblastoma is one of the most common ophthalmic neoplasms affecting children worldwide. Since its recent introduction, superselective ophthalmic artery injection of chemotherapy with melphalan has significantly reduced the need for enucleation in patients with advanced disease and also shown to have minimal adverse effects on visual acuity as compared to the conventional therapy. Although no severe complications resulting in strokes or deaths have been reported, this treatment modality is not without diffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…[ 15 – 17 ] In our patients, 7 cases have bradycardia and hypotension which respond well to intravenous epinephrine bitartrate infusion. The symptom is similar to Klumpp's previous report: [ 18 ] at first, the patients end-tidal CO 2 suddenly decreased and airway resistance increased, followed by a subsequent deterioration in the oxygen saturation. The O 2 saturation and the End-tidal CO 2 became normal after intravenous epinephrine bitartrate infusion, while the patients had hypotensive.…”
Section: Discussionsupporting
confidence: 89%
“…[ 15 – 17 ] In our patients, 7 cases have bradycardia and hypotension which respond well to intravenous epinephrine bitartrate infusion. The symptom is similar to Klumpp's previous report: [ 18 ] at first, the patients end-tidal CO 2 suddenly decreased and airway resistance increased, followed by a subsequent deterioration in the oxygen saturation. The O 2 saturation and the End-tidal CO 2 became normal after intravenous epinephrine bitartrate infusion, while the patients had hypotensive.…”
Section: Discussionsupporting
confidence: 89%
“…16 Klumpp et al presented a case of hemodynamic instability and hypotension induced by IAC. 17 In a series of 198 IAC applications involving 70 eyes, Shields et al reported eyelid edema in 5%, ptosis in 5%, cutaneous hyperemia in 2%, vitreous hemorrhage in 2%, OA spasm in 2%, partial choroidal ischemia in 2%, and OA occlusion in 2%. 18 Tsimpida et al reported that reasons for vision loss after IAC were retinal detachment, diffuse choroidal ischemia, and sectoral choroidal ischemia involving the foveola.…”
Section: Discussionmentioning
confidence: 99%
“…When these changes occur, the provider must stop the manipulation of the catheter immediately. The hypotension can present from 13-37 minutes [ 11 ], while the bradycardia might persist despite the treatment with atropine [ 5 ]. No reports to date have documented the requirement of a pacemaker.…”
Section: Discussionmentioning
confidence: 99%